SOCIAL-PSYCHOLOGICAL FEATURES OF THE INFLUENCE OF PASSION IN THE CAREER CHOICE OF EARLY ADOLESCENTS (Universal International Scientific Journal, 2026)
Choosing a career is one of the most important decisions in a person's life, directly affecting his future lifestyle, professional success and personal well-being. Today, the dynamic development of society, the volatility of the labor market and the diversification of professions require young people to consciously prepare for the process of choosing a career.
Keywords: socio-psychological characteristics, adolescent psychology, early adolescence, career choice, professional activity, interests (hobbies), motivation, social environment, family influence, peer influence, personal development, self-awareness, abilities and talents, professional orientation, professional identification, psychological factors, decision-making, self-assessment, socialization, education system, future plans